The dawn of active genetics - Bier, Ethan (Henry Stewart Talks, 2018)
CRISPR/Cas9 technology, The mutagenic chain reaction (MCR), Mendelian vs MCR inheritance, Gene-drive strategies in mosquitoes, Logistic spread of an MCR element, ERACR gene-drive reversal elements, CHACR elements, e-CHACR as an alternative strategy, Split-drive CopyCat elements, Safety precautions used for gene-drive experiments